Watchman Watcher / Ashraf Ab Aziz and Ahmad Firuz Mohd Fadhil - Ab Aziz, Ashraf; Mohd Fadhil, Ahmad Firuz (2005)
Nowadays, laziness of security guard is the problem is encounter In employers in Malaysia. They do not effectively work on their duty that keeps their guard area in sale and secure. Almost if all security guard in Malaysia, working at night does not complete their duties and sleeping in the time of work. Employers in Malaysia should look seriously of this problem where their guard keeps their property in not secure condition and it will be losses to employers. So. our project ‘watchman watcher‘ is a alternative way to solve this problem with low cost and effective due to settle up the problem. This project can be used in offices, stores and warehouses during night to check whether the guard (watchman) is on duty or not.